2013
DOI: 10.2166/wst.2012.447
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale demonstration of the hybrid zero-valent iron process for treating flue-gas-desulfurization wastewater: Part II

Abstract: The hybrid zero-valent-iron (hZVI) process is a novel chemical treatment process that has shown promise for removing heavy metals and nutrients from industrial wastewaters. In this study, a pilot-scale demonstration was conducted to continuously treat 3.8-7.6 L/min (1-2 gpm) of the flue-gas-desulfurization (FGD) wastewater at a coal-fired power plant for 5 months. In this paper, a spike test was conducted to evaluate performance of the hZVI process for removing selected toxic metals at artificially elevated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…This impression is supported by articles which reported on quantitative removal of species (e.g., 1,2-dichloroethane, dichloromethane, methylene blue, triazoles) which were proven to be not reducible by Fe 0 [83][84][85]. The performance of Fe 0 materials for water treatment has been adapted in recent years via multiple different methodologies, for a wide range of applications, including: (i) decreasing the particle size to nano-scale in order to enhance the reactivity of the material as a function of mass [86]; (ii) embedding noble bimetallic particles into the Fe 0 structure in order to improve the galvanic properties of the material [87]; (iii) embedding Fe 0 into appropriate porous support materials [14,48]; and (iv) embedding Fe 0 with complimentary adsorbent materials [88][89][90]. In addition, other metallic elements (namely Al has typically been demonstrated as superior due to its cost-effectiveness, bio-compatibility and long-term reactivity under natural conditions [96,97].…”
Section: /H2o System For Contaminant Mitigationmentioning
confidence: 99%
See 3 more Smart Citations
“…This impression is supported by articles which reported on quantitative removal of species (e.g., 1,2-dichloroethane, dichloromethane, methylene blue, triazoles) which were proven to be not reducible by Fe 0 [83][84][85]. The performance of Fe 0 materials for water treatment has been adapted in recent years via multiple different methodologies, for a wide range of applications, including: (i) decreasing the particle size to nano-scale in order to enhance the reactivity of the material as a function of mass [86]; (ii) embedding noble bimetallic particles into the Fe 0 structure in order to improve the galvanic properties of the material [87]; (iii) embedding Fe 0 into appropriate porous support materials [14,48]; and (iv) embedding Fe 0 with complimentary adsorbent materials [88][89][90]. In addition, other metallic elements (namely Al has typically been demonstrated as superior due to its cost-effectiveness, bio-compatibility and long-term reactivity under natural conditions [96,97].…”
Section: /H2o System For Contaminant Mitigationmentioning
confidence: 99%
“…No consideration of these key issues has led to controversial reports which render the assessment of progress in designing Fe [8,9,54,58,[88][89][90][124][125][126]. In particular, the usefulness of mixing Fe 0 and inert (anthracite, pumice, sand) or reactive but non-expansive (Fe3O4, MnO2, TiO2) materials is still controversially discussed [125,127,128].…”
Section: /H2o Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Yong H. Huang explored the removal performance of heavy metals in desulfurization wastewater using hybrid zerovalent iron. 7,8 The results revealed that the removal efficiencies of Se and Hg were more than 99%; Lin Cui studied electrolysis-electrodialysis process removing chloride ion from wet ue gas desulfurization wastewater and the removal efficiency reached 83.3%; 9 Na Yin investigated the process feasibility of ultraltration-nanoltration-reverse osmosis applying for desulfurization wastewater treatment, which could produce sulfuric acid and ammonium salt at the same time, results showed that the process could treat desulfurization wastewater to the discharge standard and the by-product purity was high. 10 On April 16, 2015, the State Council of China issued the "Water Pollution Control Action Plan", to emphasize the management of various types of water pollution.…”
Section: Introductionmentioning
confidence: 99%